Transgenic Drosophila Expressing Active Human LH Receptor in the Gonads Exhibit a Decreased Fecundity: Towards a Platform to Identify New Orally Active Modulators of Gonadotropin Receptor Activity - Amir Mahamid; David Ben-Menahem (MDPI AG, 2024)
Background/Objectives: The gonadotropins luteinizing hormone (LH) and follicle-stimulating hormone (FSH) and their receptors are major regulators of reproduction in mammals and are absent in insects. We previously established transgenic Drosophila lines expressing a constitutively active human LH receptor variant (LHRD578Y) and the wild-type receptor (LHRwt; inactive in the absence of an agonist). That study showed that ubiquitously expression of LHRD578Y-but not of LHRwt-resulted in pupal lethality, and targeted expression in midline cells resulted in thorax/bristles defects. To further study the Drosophila model for an in vivo drug screening platform, we investigated here whether expressing LHRD578Y in the fly gonads alters reproduction, as shown in a transgenic mice model. Methods: The receptor was expressed in somatic cells of the gonads using the tissue-specific traffic jam-Gal4 driver. Western blot analysis confirmed receptor expression in the ovaries. Results: A fecundity assay indicated that the ectopic expression of LHRD578Y resulted in a decrease in egg laying compared to control flies carrying, but not expressing the transgene (~40% decrease in two independent fly lines, p < 0.001). No significant reduction in the number of laid eggs was seen in flies expressing the LHRWT (<10% decrease compared to non-driven flies, p > 0.05). The decreased egg laying demonstrates a phenotype of the active receptor in the fly gonads, the prime target organs of the gonadotropins in mammals. We suggest that this versatile Drosophila model can be used for the pharmacological search for gonadotropin modulators. Conclusions: This is expected to provide: (a) new mimetic drug candidates (receptor-agonists/signaling-activators) for assisted reproduction treatment, (b) blockers for potential fertility regulation, and (c) leads relevant for the purpose of managing extra gonadotropic reported activities.